From the Deathbed to the Register: Administering the Dead in the Early Nineteenth-Century Ottoman Empire - Gundogdu, Cihangir; Balsoy, Gulhan (Oxford Univ Press, 2025)
The Ottoman Empire instituted state-sponsored inspection and registration of the dead in the early nineteenth century. For the first time, medical professionals known as tabib were hired to investigate the causes of deaths within Istanbul's perimeters. This initial surveillance effort in 1838-39 created the city's first two death registers, comprising 9,500 individual cases in total. In the light of these records, the current study investigates the surveillance of death and disease in the nineteenth-century Ottoman Empire by situating it within the global context of registering the dead, examining the first Ottoman regulations to detail the procedures concerning the registration process and identifying the professionals engaged therein. Since the primary concern of the present study is an investigation of the administration of the dead and medical surveillance, we emphasise the discrepancies observed in the registration process and scrutinise both the medical categories used and the registering physicians' professional backgrounds.
Keywords: Ottoman History; History Of Medicine; Epidemic Diseases; Medical Surveillance; Death Registers